Research in Islamic Economics and Finance in Malaysia: A Review - Muhamad Muda; Fara Madehah Ahmad Farid; Nursilah Ahmad; Hanim Hj Misbah; Nor Haziah Hashim; Zurina Kefeli@ Zulkefli (Universiti Sains Islam Malaysia, 2024)
This paper evaluates and analyses contents on several selected journals on Islamic economics and finance in Malaysia between 1977-3003. A brief introduction on the purpose, importance and structure of the journals are highlighted followed by its history, within the first part of the article. This paper also covers the background of the journals, the methodology and the reviews the relevant articles. Apart from that descriptive statistics concerning the classification of field of study of study each journal and subtopics of articles reviewed were also presented. A brief contents analysis of Islamic economics system, Islamic finance and banking, Islamic economic development and Islamic management articles were discussed to examine its prospect for research in the future. This review found that the scope and areas of interest, as indicated by the publications are narrow and few. This paper concludes with a discussion on the needs to proliferate the research and publication in the areas of Islamic banking and finance, Islamic economics and Islamic management.